Women Participation in Leadership Positions in Mtubatuba Local Municipality, South Africa - Nokuthula Ntuli; Nokukhanya N Jili; Mzwandile R Xaba (Universitas Gadjah Mada, 2023)
Introduction/Main Objectives: The article aimed to explore the nature, level and extent of women participation in administrative and political leadership in the Mtubatuba Local Municipality (MLM). It adopted the socialist feminism theory as its framework. Research Methods: Qualitative research methods was used in which data were collected using semi-structured interviews from eight women working in the Mtubatuba Local Municipality's political and administrative structures selected using purposive sampling methods. Thematic analysis was employed to analyze data received from participants. Novelty: The researchers found that women's leadership in both the administrative and political realms of the MLM was a struggle that demanded endurance against various harsh forces mainly stemming from culture and patriarchy. Finding/Results: The article concluded that the excessive prevalence of gender inequality and male dominance in leadership was worsened by the fact that the few women in management and leadership were not seriously considered in decision-making. This was regardless of the existence of many national and local level policies and strategies aimed at elevating women into leadership with the agenda of attaining gender equality. Conclusion: Political organizations in the Municipality failed to mobilize support for the policies that promote of advancement of women.